Studi Pengolahan Limbah Usaha Mandiri Rumah Tangga dan Dampak Bagi Kesehatan di Wilayah Kenjeran, Surabaya - Dahruji Dahruji; Pipit Festy Wilianarti; Totok Totok Hendarto (Universitas Muhammadiyah Surabaya, 2017)
At this time the development of the industry in Indonesia is growing rapidly, there are currently large and small industries. An assortment of chemical industry, paper, textiles and cement. The small industry such as industry know. Many industries can generate positive and negative impacts. The positive impact of the industry, among others, the creation of jobs and the use of new technologies in various fields. The negative effects derived from industrial waste in the form of waste, liquid waste containing substances that are harmful to the surrounding community, so that the disposal of waste produces a toxic substance that causes the growth of bacteria that breed. With the indiscriminate disposal of waste fluids can cause problems for humans share, environment and water, can grow germs or other germs harmful to humans, would be susceptible to various diseases due to the influence of chemicals that pollute the river. Long-kelaman waste fluid change color to dark brown and smelly, and the stench is going to result in respiratory problems for people around. (Atinah fatal 2007).The research method using descriptive research method, with consecutive sampling technique to sample 21 people. Analysis using the percentage description. Results obtained 17 percent of skin disorders, diarrhea 2 percent, and laboratory values averaged COB try the 1 meter including pemcemaran being.With the existence of this study is expected an increase of knowledge in the management of household waste small industries.